Systemic evaluation of various haemostatic agents following local application prior to direct pulp capping - Franklin Garcia-Godoy; Peter E. Murray (Universidade Estadual de Campinas, 2015)
Limited physiological information is available regarding the role of hemostatic agents to control the success of direct pulp capping treatment in order to help save vital pulps from pulpotomy, pulpectomy or extraction. The aim of this study was to test whether placement of various hemostatic agents would alter short-term pulp healing following direct pulp capping. Class V cavity preparations with pulp exposures were prepared in 31-nonhuman primate teeth, pulp hemorrhage was controlled by placement of epinephrine, Consepsis®, sodium hypochlorite or combinations of these agents. Each exposure was then direct capped with composite resin and then observed immediately or after 13, and 28-days. Histological examination of pulp healing was conducted according to ISO standards for pulp inflammation, soft tissue organization, reactionary and reparative dentin bridge formation. Physiological measurement of heart rate and blood pressure were continuously recorded during the three operative procedures. Local pulp treatment with the various hemostatic agents did not alter systemic blood pressure or heart rate during local pulp application. All hemostatic treatments provided acceptable biocompatibility. Minor differences in pulp healing were observed, but there were no statistically significant differences between treatments (Pe"0.05). We conclude that hemostatic treatment had little effect on systemic pulp physiology or healing.